Circ_0068087 Silencing Ameliorates Oxidized Low-Density Lipoprotein-Induced Dysfunction in Vascular Endothelial Cells Depending on miR-186-5p-Mediated Regulation of Roundabout Guidance Receptor 1 - Li, Shuanghong; Huang, Tao; Qin, Limin; Yin, Luchang (Frontiers in Cardiovascular Medicine, 2021)
Background: Circular RNAs (circRNAs) are endogenous non-coding RNAs involved in the progression of atherosclerosis (AS). We investigated the role of circ_0068087 in AS progression and its associated mechanism. Methods: 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay, flow cytometry, and enzyme-linked immunosorbent assay (ELISA) were performed to analyze the viability, apoptosis, and inflammatory response of HUVECs, respectively. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blot assay were performed to measure the expression of RNA and protein. Cell oxidative stress was analyzed using commercial kits. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were conducted to verify the interaction between microRNA-186-5p (miR-186-5p) and circ_0068087 or roundabout guidance receptor 1 (ROBO1). Results: Oxidized low-density lipoprotein (ox-LDL) exposure up-regulated circ_0068087 level in HUVECs. ox-LDL-induced dysfunction in HUVECs was largely attenuated by the silence of circ_0068087. Circ_0068087 negatively regulated miR186-5p level by interacting with it in HUVECs. Circ_0068087 knockdown restrained ox-LDL-induced injury in HUVECs partly by up-regulating miR-186-5p. ROBO1 was a downstream target of miR-186-5p in HUVECs. Circ_0068087 positively regulated ROBO1 expression by sponging miR-186-5p in HUVECs. MiR-186-5p overexpression exerted a protective role in ox-LDL-induced HUVECs partly by down-regulating ROBO1. Conclusion: Circ_0068087 interference alleviated ox-LDL-induced dysfunction in HUVECs partly by reducing ROBO1 expression via up-regulating miR-186-5p.